SISTEM INFORMASI PENGOLAHAN DATA ASRAMA MAHASISWA UNIVERSITAS ANDALAS - Rahmadini Darwas; Gusrino Yanto; Merisa Putri (Universitas Negeri Padang, 2018)
The Student Dormitory is a living quarters dedicated to a group of people currently undergoing education at a university or college. Data processing dormitory not using data storage media automatically (database) so that cause often found mistake in recording of payment report between administration clerk with bank slip which owned by student consequently check out student process becomes delayed. The number of dormitory data archives be it student data in the form of check in form and dormitory payment data in the form of bank slips that stacked make the administration difficult in making report recapitulation. So that requires a high level of accuracy and a long time in search data and making the report to present information to the parties concerned. With this application is expected to increase employee productivity in the administration and improve information services to students, so that students can complete the administrative process quickly